The Mediating Effect: How Team Performance Absorbs Organizational Resources for Project Success in the Software Engineering Industry - Saputra, Dony; binti Shafie , Dalili Izni; Orlin Baptista Yuleoni (Jurnal Manajemen Teknologi, 2025)
Abstract. The rapid growth of Indonesia's IT industry is accompanied by a high rate of project failures, prompting a critical examination of traditional success factors. While organizational culture, top management support, and team competence are widely advocated, their direct impact remains ambiguous. This study examines the intricate relationship between these factors, team performance, and project success within Indonesian software companies. Using a quantitative cross-sectional survey, data were collected from 67 professionals in a Jakarta-based IT company and analyzed with PLS-SEM. The results reveal a pivotal finding: organizational culture and competence do not directly affect project success but exert their influence entirely through the mediating mechanism of team performance. Conversely, the direct and indirect effects of top management support were found to be non-significant. This study uniquely establishes team performance as the critical mediator, challenging linear models and offering a more nuanced understanding of project success pathways. The practical contribution is a strategic reorientation for managers and HR, emphasizing that investments in collaborative team development and a supportive culture are more consequential for achieving project outcomes than relying solely on top-down directives or individual competencies. This research provides a validated framework for enhancing project sustainability in dynamic IT environments. Keywords: Organizational culture; top management support; competence; team performance; project success; information and communication technology